Evaluation of immature platelet fraction as a marker of dengue fever progression. (September 2021) - Looi, Kah Wai; Matsui, Yukari; Kono, Mari; Samudi, Chandramathi; Kojima, Nozomi; Ong, Jin Xu; Tan, Chin Aun; Ang, Chong Siang; Tan, Peter Hao Yuan; Shamnugam, Hemalatha; Sekaran, Shamala Devi; Syed Omar, Sharifah Faridah; et al.
Highlights: Immature platelet fraction (IPF) is a precursor indicating platelet formation, and precedes platelet recovery by 3 days. IPF is higher in patients with severe dengue compared with patients with non-severe dengue on days 3–5 of illness. IPF could be an early recovery indicator of thrombocytopenia in dengue. Further studies are needed on the association between IPF trends and early disease progression. ABSTRACT: Objectives: Progression of dengue is often associated with thrombocytopenia resulting from viral-induced bone marrow suppression and immune-mediated peripheral platelet consumption. Immature platelet fraction (IPF), which can be measured using a haematology analyser, is a precursor indicating platelet formation in the bone marrow. This study evaluated the trend of IPF as an early recovery indicator of platelets in dengue patients with thrombocytopenia, and its relationship with severe dengue in conjunction with reticulocyte count. Methods: Hospitalized patients with dengue were enrolled and followed-up daily until discharge. Blood investigations included daily full blood counts and IPF measured using a haematology analyser. Results: In total, 287 patients with confirmed dengue were enrolled in this study, 25 of whom had severe dengue. All patients had a decreasing trend in platelet count in the first week of illness, concomitant with an increasing trend in the percentage of immature platelets to total platelets (IPF%) for more than 3 days prior to platelet recovery. IPF% was significantly increased in patients with severe dengue compared with patients with non-severe dengue on days 3–5 after the onset of fever. Reticulocyte count increased significantly in patients with severe dengue on day 5. Conclusions: IPF can be utilized as an early recovery indicator of platelets in patients with dengue and thrombocytopenia.